A Comparison of the CMIP6 midHolocene and lig127k Simulations in CESM2. Issue 11 (4th November 2020) - Otto‐Bliesner, Bette L.; Brady, Esther C.; Tomas, Robert A.; Albani, Samuel; Bartlein, Patrick J.; Mahowald, Natalie M.; Shafer, Sarah L.; Kluzek, Erik; Lawrence, Peter J.; Leguy, Gunter; Rothstein, Mathew; Sommers, Aleah N.
Abstract: Results are presented and compared for the Community Earth System Model version 2 (CESM2) simulations of the middle Holocene (MH, 6 ka) and Last Interglacial (LIG, 127 ka). These simulations are designated as Tier 1 experiments ( midHolocene and lig127k ) for the Coupled Model Intercomparison Project phase 6 (CMIP6) and the Paleoclimate Modeling Intercomparison Project phase 4 (PMIP4). They use the low‐top, standard 1° version of CESM2 contributing to CMIP6 DECK, historical, and future projection simulations, and to other modeling intercomparison projects. The midHolocene and lig127k provide the opportunity to examine the responses in CESM2 to the orbitally induced changes in the seasonal and latitudinal distribution of insolation. The insolation anomalies result in summer warming over the Northern Hemisphere continents, reduced Arctic summer minimum sea ice, and increased areal extent of the North African monsoon. The Arctic remains warm throughout the year. These changes are greater in the lig127k than midHolocene simulation. Other notable changes are reduction of the Niño3.4 variability and Drake Passage transport and a small increase in the Atlantic Meridional Overturning Circulation from the piControl to midHolocene to lig127k simulation. Comparisons to paleo‐data and to simulations from previous model versions are discussed. Possible reasons for mismatches with the paleo‐observations are proposed, including missing processes in CESM2, simplifications in the CMIP6 protocols for these experiments, and dating and calibration uncertainties in the data reconstructions. Plain Language Summary: The modeling of past climates, using physically based tools and comparing to paleo‐observations, is increasingly seen as a strong test of the models that are used for the projection of future climate changes. We report on simulations by one of the latest large‐scale climate models, the Community Earth System Model version 2 (CESM2), for the two most recent warm epochs: the current interglacial—the Holocene, which began 11, 650 years ago ‐ and the previous interglacial—the Last Interglacial, which extended from 129, 000 to 116, 000 years ago. The simulations find summer warming over the Northern Hemisphere continents, reduced Arctic summer sea ice, and increased areal extent of the North African monsoon. Cryospheric and oceanic feedbacks drive year‐round Arctic warmth. The CESM2 middle Holocene and Last Interglacial simulations are an important resource for the community participating in the Coupled Model Intercomparison Project phase 6 (CMIP6). Key Points: Orbital configurations for 6 ka and 127 ka force enhanced Northern Hemisphere summer insolation versus the preindustrial, with greater anomalies at 127 ka This forcing in CESM2 yields summer warming over Northern Hemisphere continents, reduced Arctic minimum sea ice, and increased extent of the North African monsoon The middle Holocene and Last Interglacial simulations provide out‐of‐sample tests of CESM2